2009
DOI: 10.1186/1475-2875-8-237
|View full text |Cite
|
Sign up to set email alerts
|

Presumptive treatment with sulphadoxine-pyrimethamine versus weekly chloroquine for malaria prophylaxis in children with sickle cell anaemia in Uganda: a randomized controlled trial

Abstract: Background: Malaria carries high case fatality among children with sickle cell anaemia. In Uganda, chloroquine is used for prophylaxis in these children despite unacceptably high levels of resistance. Intermittent presumptive treatment with sulphadoxine-pyrimethamine (SP) has shown great potential for reducing prevalence of malaria and anaemia among pregnant women and infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…The CQ remains available in Uganda, and in fact it continues to be recommended for regular chemoprophylaxis in children with sickle cell disease. 42 Very recently, the prevalence of parasites with the CQ-sensitive pfcrt K76 genotype increased markedly in Tororo, suggesting a decrease in community use of CQ.…”
Section: Discussionmentioning
confidence: 99%
“…The CQ remains available in Uganda, and in fact it continues to be recommended for regular chemoprophylaxis in children with sickle cell disease. 42 Very recently, the prevalence of parasites with the CQ-sensitive pfcrt K76 genotype increased markedly in Tororo, suggesting a decrease in community use of CQ.…”
Section: Discussionmentioning
confidence: 99%
“… Massaga 2003 Anaemia not part of the inclusion criteria. Nakibuuka 2009 No control group ‐ comparing two malaria treatment regimes. Rohner 2010 Anaemia not part of the inclusion criteria.…”
Section: Characteristics Of Excluded Studies [Ordered By Study Id]mentioning
confidence: 99%
“…A Cochrane review of malaria prophylaxis for patients with SCD concluded that prophylaxis is beneficial, with fewer episodes of malaria, higher mean hemoglobin concentrations, fewer transfusions, fewer hospital admissions, and fewer sickle cell crises in patients receiving prophylaxis [ 6 ], but the review included only 2 small studies, one from Kampala in 1965, which involved administration of chloroquine plus benzathine penicillin for 12 months [ 7 ], and one from Nigeria in 2003, in which 97 patients were randomized to receive daily proguanil therapy, weekly pyrimethamine therapy, or placebo for 9 months [ 8 ]. Studies not in the review included a placebo-controlled trial of 60 patients in Senegal that showed that monthly sulfadoxine-pyrimethamine (SP) treatment during the transmission season was well tolerated and reduced morbidity [ 9 ]; a study in Uganda, with just 1 month of follow-up, that suggested that weekly chloroquine therapy was less effective than monthly SP therapy [ 10 ]; and a study in Nigeria that indicated that weekly mefloquine (MQ) was well tolerated and more effective than daily proguanil [ 11 ]. Several small surveys of patients with SCD in Nigeria who received daily proguanil or weekly pyrimethamine prophylaxis have found that malaria parasitemia is common and attributed this finding to poor compliance and resistance [ 12 – 14 ].…”
mentioning
confidence: 99%